DEVELOPMENT AND VALIDATION OF LIQUID CHROMATOGRAPHY COUPLED WITH TANDEM MASS SPECTROMETRY METHOD FOR ESTIMATION OF LENVATINIB IN HUMAN PLASMA - I, Srikanth; A, Prameela Rani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was to develop and validate a liquid chromatography–tandem mass spectrometry (LC–MS/MS) for the quantification of lenvatinib (LT) in human plasma. Methods: A simple, sensitive and specific LC–MS/MS method was developed for quantification of LT in human plasma using LTD4 as internal standard (IS). The analytical method consists of liquid–liquid extraction of plasma sample followed by the determination of LT by a LC–MS/MS. The analyte was separated on a Zorbax Eclipse XDB-C18 (150×4.6 mm, 5 μ) column with an isocratic mobile phase of acetontrile:0.1% formic acid (80:20 v/v) at a flow rate of 0.6 mL/minutes. The protonated ions were formed by a turbolon spray in a positive mode were used to detect analyte and IS. The MS/MS detection was made by monitoring the fragmentation of m/z 427.10→370.10 for LT and m/z 430.30→370.10 for IS on a MS. Result: The method was validated with the correlation coefficients of (r2) ≥0.995 over a linear concentration range of 10.20-501.60 pg/mL. This method demonstrated intra- and inter-day precision within 1.06-2.42% and 0.03-0.55% and accuracy within 95.64-100.08% and 97.16-100.07%. Conclusion: This method is suitable and convenient to pharmacokinetics and bioavailability studies for estimation of LT in biological samples by LC–MS/MS.